Perception and Practices of Pica among Pregnant Women in the La Nkwantanang- Madina Municipal - Hommey, J. (University of Ghana, 2016)
Introduction Research from several Western countries has revealed that most pregnant women are likely to engage in pica practice. Despite the dangers associated with pica and its prevalence in various communities across the world and particularly in Ghana, most pregnant women still engage in the practice.Investigation was conducted to assess perception and practices of pica among pregnant women in La Nkwantanang-Madina Municipal. Methods A descriptive cross –sectional design was used and data was collected quantitatively using structured questionnaire. A total number of 330 pregnant women were selected using a systematic random sampling technique from population of pregnant women who seek antenatal care from Pentecost Hospital and Madina Polyclinic (Kekele) maternity block. The data was analyzed statistically using SPSS software version 21. The association of consumption of non-food items and reasons for practicing pica were determined with the use of Chi square statistics. Results The results revealed that majority of the pregnant women (86.97%) had heard about pica practices from various sources (home, television, hospitals/clinics, churches, schools and markets). The results also revealed that 276 pregnant women (83.64%) practised pica and the most non-food items identified to be consumed were Pagophagia (ice, 61.52%), Geophagia (white clay, 52.12%) and charcoal (21.52%) and were mostly consume during first trimester (28.48%) and second trimester (28.79%). The proportion of pregnantwomen who practised pica was observed to be 84% of the population. An association of consumption of non-food items and reasons for practicing pica showed that taste (P=0.003), smell (P=0.00), environmental factors (P=0.000), cravings for the non-food items (P=0.004), to control vomiting (P=0.040) and consumption for satisfaction (P=0.001) were significantly associated with pica practice. The results also revealed that some pregnancy symptoms such as vomiting (P=0.000), headaches (P=0.000), itching of skin (P=0.000), dizziness (P=0.015), spitting (P=0.00) were significantly associated with the practice of pica of the pregnant women. The analysis also showed a statistically significant association of pregnant women who have received education on the effects of pica practices and the consumption of the non-food items (P=0.045). Conclusion The study accentuates the need for intensive monitoring, education and counseling for pregnant women by healthcare professions on pica practices and its effects. Xi, 79p: ill
Thesis(MSc)-University of Ghana, 2016
Keywords: Pica; Pregnant Women; Perception; Practices